SDR: A new method to assess the natural vulnerability to contamination of granular unconfined aquifers - Francisco, Richard Fonseca [UNESP]; Braga, Antonio Celso de Oliveira [UNESP]; Albuquerque Filho, José Luiz (My University, 2019)
In view of increase in the number of contaminated areas, which compromise the groundwater quality and constitute risks to human health, it is essential to establish instruments for land use planning and management, aiming at the groundwater protection. Thus, the aim of this work was to develop and apply, experimentally, a new method to assess the natural vulnerability to contamination of granular unconfined aquifers. For this purpose, longitudinal unit conductance (Si), slope (D) and recharge (R) factors were selected, weighted and integrated – SDR method, with support of Multicriteria Evaluation (MCE) and geoprocessing techniques operated in GIS environment. Located in the Rio Claro municipality, São Paulo State, Brazil, the Rio Claro Aquifer was chosen to apply this new evaluation method. With respect to result, the entire study area presented high natural vulnerability, which is compatible with those reported in previous studies. Due to robust result, the practical use and the reduced number of required parameters, the SDR method represents a new alternative to traditional methods and may play an important role to granular unconfined aquifers protection.
SDR: Um novo método para avaliar a vulnerabilidade natural à contaminação de aquíferos livres granulares
Keywords: Longitudinal unit conductance; Multicriteria evaluation; Rio Claro aquifer; SDR method; Vulnerability